Beyond religious instruction: Transformative strategies of Islamic religious education teachers for internalizing religious moderation values in multicultural vocational schools - Dhea Ananda; Ilham Ilham; Masita Masita (Fakultas Tarbiyah, Universitas Ibrahimy, 2026)
Strengthening religious moderation has become a national strategic priority in addressing the complexity of religious diversity, growing social fragmentation, and the challenges of digitalization that shape students’ religious perspectives. This study aims to comprehensively examine the transformative strategies employed by IRE (Islamic Religious Education) teachers in internalizing religious moderation values within a multicultural school environment, as well as to identify the factors influencing their effectiveness. Employing a qualitative approach with a case study design, this research collected data through in-depth interviews, observations, and document analysis. The findings reveal that the internalization of religious moderation is implemented through systemic, integrative, and sustainable transformative strategies, including teacher role modeling, habituation practices, integration of moderation values into formal learning processes, dialogical approaches, and the optimization of religious activities. Furthermore, the study demonstrates that the success of value transformation is shaped by the interplay of institutional, social, and pedagogical factors, encompassing school policy support, leadership capacity, teachers’ professional competence, family engagement, and students’ social environmental characteristics. Nevertheless, the pervasive influence of digital media and the diversity of students’ prior understanding of religious moderation remain significant challenges that require adaptive and context-sensitive pedagogical frameworks. This study contributes to the advancement of religious moderation scholarship by providing a contextual analysis of IRE teachers’ transformative strategies in fostering religious moderation values within vocational education, while highlighting the dynamic factors that shape its implementation.